Recycling of Concrete Demolition Waste Powder as a Sustainable Material in Portland Cement Pastes Modified with Nano-silica - Darweesh, H.H.M. (Journal of Sustainable Materials Processing and Management, 2022)
In recent years, researchers dedicated themselves to explore the possibility of introducing concrete waste powder (CWP) into Portland cement as a sustainable material for Portland cement. To optimize the effect of CWP on cement-based materials, this paper uses nano-silica (NS) to improve the hydration and mechanical properties of cement-based materials with CWP. Results indicated that after adding NS into CWP cement pastes, the setting time of cement pastes was significantly reduced, while the early rate of hydration and hydration heat increased. Besides, the mechanical strengths of the cement pastes increased as CWP replaced at the expense of the cement up till 15 wt. % and, then decreased, while nanosilica (NS) addition can compensate the mechanical strength loss caused by CWP as supplementary cementing materials. The higher ratios of CWP than 15 wt. % increased the pore volume or porosity. In contrast, NS in CWP blended cement significantly decreased the porosity, and increased the proportion of harmless pores. Hence, NS reduced the porosity, which in turn improved and enhanced the bulk density and mechanical strengths. The optimum amount of NS is 2.5 wt. % which resulted in the best results. The heat of hydration of the different cement batches in the two groups adversely affected with the incorporation of CWP, but little improved with NS. The obtained results were confirmed by the ultrasonic pulse velocity (USPV) test, where the cement batch PP15 (Gp I) and PS2.5 (Gp II) achieved the highest conformance.